The Analysis of Learning Implementation Plan in Vocational Subjects Based on 2013 Curriculum - Hamid, MA; Nurtanto, M; Fawaid, M (INVOTEC, 2018)
The qualified teacher is teacher who has the standards of educator that has capability of their materials according to the standard of the contents and carry out the learning process according to the standard of the process. Learning Implementation Plan (LIP) is the administration prepared teachers before carrying out the learning process. This research aims to know the quality of the LIP who made by teachers. This research is a descriptive qualitative. The data were collected through questionnaire, document’s noting, and interviews method. The research subjects are vocational teachers in SMK Negeri 1 Cilegon. The results of this research shows that (1) the completeness of the components 63.63; (2) conformity between components 85.7; (3) feasibility of competence 100; (4) feasibility of the indicators and the achievement of basic competencies 100; (5) feasibility of the learning objectives 80; (6) formulate learning objectives 75; (7) choosing and organizing the learning material 80; (8) feasibility of the learning activities 84.6; (9) selection of learning methods 100; (10) selection of media, tools and learning resources 85.71; and (11) the feasibility assessment 85.7, so that the average was 85.5 with good qualifications. The LIP is structured properly can increase the effectiveness of learning in the classroom and improve the quality of teaching and graduates are in accordance with the needs of the ASEAN Economic Community.